Middle school teacher pedagogic competency map for private vocational school in Wanareja Cilacap - Rahmat Basuki; Edhy Susatya; Bambang Noor Achsan Kristiyanto (Universitas Ahmad Dahlan, 2021)
This study aims to map the acquisition of teachers’ pedagogical competence at private vocational high schools Wanareja, Cilacap, Central Java. This research used quantitative method. We involved 60 teachers from four private vocational schools as the research subject. We delivered a Likert-scale questionnaire to assess the pedagogical competence. Then, we analyzed the data using non-parametric inferential statistics. The results showed that the pedagogical competence of private vocational school teachers in Wanareja on ten aspects of pedagogical competence had different categories in each aspect. The aspect of mastering the students’ characteristics was very sufficient (55%). The aspect of mastering the learning theory was good (44%) and very sufficient (40%). The aspect of developing a curriculum was good (48%). The aspect of organizing learning was good (63%). The aspect of using ICT in learning was very sufficient (51%). The aspect of developing the students’ potential was good (44%). The aspect of effective communication and politeness was good (63%). The aspect of conducting an assessment was sufficient (53%). The aspect of utilizing the results of the assessment for the benefit of learning was very sufficient (53%). And finally, the aspect of doing reflective action was sufficient (68%). The implementation of the pedagogical competence of private vocational school teachers in Wanareja has not been evenly distributed in all aspects of competencies and efforts to improve teacher pedagogical competence has not been maximized.